Rancang Bangun Rangka dan Penggerak Mesin FDM Berbasis Arduino Tipe XZ-Head - Radhi Ariawan; Nur Akhlis Sarihidaya Laksana; Unggul Satria Jati; Roy Aries Permana Tarigan (Infotekmesin, 2023)
FDM is an AM method that is currently being developed due to the flexibility of the object geometry that can be formed. This study aims to design the frame and drive of the XZ Head type FDM engine. Stress simulation was carried out to determine the safety factor in the frameXZ design. Lead screw parameters in the form of torque, shear stress, axial stress, and critical load were calculated to determine the torque requirement of the driving motor. The value of the linear axis of the stepper motor was calibrated to determine the dimensions of the printed output. Based on the simulation, the dynamic and static stresses on the XZ frame were 1.9 MPa and 2 MPa. The yield strength was 55 MPa with a safety factor of 28. The results of the calculation of the lead screw torque (TR) and (TL) were 18.27 N.mm and 6.60 N.mm. The calculated nominal shear stress of the screw () was 0.43 N/mm2, the axial loading stress () was -0.62 N/mm2, and the critical load (Wcr) was 9986.41 N. The difference in dimensions of the measurement results in the X and Z planes was 0.22 and 0.17 mm larger than the target dimensions of 20 mm.